2016
DOI: 10.1038/ni.3484
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cell function in the context of adaptive immunity

Abstract: Innate lymphoid cells (ILCs) are a family of innate immune cells that have diverse functions during homeostasis and disease. Subsets of ILCs have phenotypes that mirror polarized T helper subsets in their expression of core transcription factors and effector cytokines. Given the similarities between these two classes of lymphocytes, it is important to understand which functions of ILCs are specialized and which are redundant in comparison to T cells. Here, we discuss genetic mouse models that have been used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 86 publications
2
73
1
1
Order By: Relevance
“…These include localization to non-lymphoid tissue, enrichment at barrier surfaces, self-renewal and rapid responses to environmental stimuli. In addition to mounting local immune responses, ILCs might influence systemic immunity by regulating adaptive responses, as described in detail in a related Perspective by Colonna and Bando in this special ILC Focus issue of Nature Immunology 32 .…”
Section: Trafficking and Tissue Residency Of Ilcsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include localization to non-lymphoid tissue, enrichment at barrier surfaces, self-renewal and rapid responses to environmental stimuli. In addition to mounting local immune responses, ILCs might influence systemic immunity by regulating adaptive responses, as described in detail in a related Perspective by Colonna and Bando in this special ILC Focus issue of Nature Immunology 32 .…”
Section: Trafficking and Tissue Residency Of Ilcsmentioning
confidence: 99%
“…This has therefore been called 'intestinal T cell selection' 30 . In contrast, stimulatory effects of MHC class II on ILC2s and ILC3s have also been described and are discussed further in the Perspective by Colonna and Bando in this Focus issue 32,83,84 .…”
Section: Effector Molecules Produced By Ilcsmentioning
confidence: 99%
“…However, one recent study by Vely et al showed that severe combined immunodeficiency (SCID) patients with mutations in the genes IL2RG and JAK3 are deficient in circulating helper ILCs and NK cells [113]. This can be explained by the requirement for IL-7 and IL-15 signaling in the survival of these cells, where IL-7 and IL-15 signals are integrated by the common γc cytokine receptor and the downstream JAK3 tyrosine kinase.…”
Section: Ilc and T Cell Complementaritymentioning
confidence: 99%
“…IL-23 enhances the production of IL-22 from group 3 ILCs (ILC3s), neutrophils, and CD4 + T cells, particularly Th17 and Th22 cells 39 . IL-22 has emerged as a central protective cytokine in the C. rodentium infection model 4042 . IL-22 is an IL-10 family member cytokine that is reported to promote barrier defense at a range of mucosal surfaces and has an indispensible role in protection against infection with C. rodentium 43,44 .…”
Section: Innate Immune Response To C Rodentiummentioning
confidence: 99%
“…Because ILC3s are the dominant source of IL-22 prior to day 5, this suggests that ILC3s and CD4 + T cells must both provide IL-22 to protect against C. rodentium infection—albeit at different tempos. Recently, using novel mouse strains to assess the relative requirement of IL-22 expression by ILC3s in the presence of T cells it was found that IL-22 production by NCR + ILC3s is redundant in immunocompetent mice, where CD4 + T cells are present during C. rodentium infection 32,42,60,65 . In view of the initial findings that implicate an important role for NCR − ILC3s early in infection, these observations imply that NCR − ILC3s might be more critical to early host protection prior to the development of IL-22-producing CD4 + T cells.…”
Section: Spatiotemporal Control Of the Interplay Between Il-22-producmentioning
confidence: 99%